Molten slag flow in an ironmaking blast furnace – a mesoscopic level investigation - X F. Dong; A Jayasekara; D Sert; R Ferreira; P Gardin; S J. Chew; D Pinson; B J Monaghan; P Zulli (The Australasian Institute of Mining and Metallurgy, 2024)
In an ironmaking blast furnace (BF), molten slag and hot metal form in the softening-melting (cohesive) zone and then trickle through the coke packed bed before being discharged from the taphole. During their downward flow, there are significant interactions occurring between liquids and other phases, such as gas and packing particles. Overall, the formation, dripping and discharging of these liquid phases, particularly molten slag, have a significant impact on BF operations in terms of furnace permeability, fuel consumption, process stability, product quality and ultimately, productivity. Hence, understanding the liquid flow behaviour in the BF lower zone is critical for designing optimal operations. In the current investigation, the flow behaviour of slag droplets was investigated at a mesoscopic level using a combined numerical and physical modelling approach. The interaction between slag and carbonaceous materials was studied using sessile drop wetting experiments, slag flow through a funnel and a high temperature packed bed and the Volume of Fluid (VOF) modelling technique. Molten slag flow and counter-current gas-slag flow in the packed bed was investigated in terms of superficial gas velocity, slag properties and packing structure. The gas-slag flow behaviour at a mesoscopic level was numerically visualised, with gas velocity gradually increased up to the flooding point. The strong interaction between gas and slag was uniquely identified, which can cause localised slag flooding as well as gas channelling. Detailed information concerning the effect on slag holdup distribution, residence time and flow patterns of wettability, slag properties and bed structure were obtained. The current investigation highlights the significant role of research at a mesoscopic level in understanding macroscopic slag flow behaviour. Gas channelling, which is a critical phenomenon in a packed bed with counter-current gas-slag flow, is predicted. It can be speculated that significant gas channelling in the BF can inevitably occur prior to operational limits being reached. In the BF process, the formation of permanent gas channelling and large slag rivulets should be avoided to maintain appropriate contact between phases and hence, furnace permeability.